Pengaruh Persepsi Ad Intrusiveness dan Content Quality terhadap Consumer Behavior dengan Variabel Mediasi Consumer Satisfaction (Studi Pada Konsumen Media Online Detikcom) - Muhammad Fathi Farhan; Osly Usman; Adnan Kasofi (Teewan Journal Solutions, 2025)
The purpose of this study is to gain new insights and analyze the influence of perceptions of ad intrusiveness and content quality on consumer behavior through consumer satisfaction as a mediation with a study on detikcom online media consumers. This study uses a quantitative method through a survey distributed with an online questionnaire, which was conducted on 240 students domiciled in DKI Jakarta with a purposive sampling technique. Through the analysis test with the Structural Equation Model (SEM) using SmartPLS, it shows that ad intrusiveness has a positive and significant influence on consumer behavior through consumer satisfaction directly and indirectly. Then content quality also has a positive and significant influence on consumer behavior through consumer satisfaction directly and indirectly. In addition, consumer satisfaction also has a positive and significant impact on consumer behavior on detikcom online media. This study shows that there is a negative perception of annoying ads on their satisfaction and behavior when doing activities on the detikcom site. In addition, content quality is one of the positive impacts in obtaining consumer satisfaction and behavior when accessing the detikcom site. This is a consideration so that the display of advertisements as a means of digital marketing on the detikcom site can be managed properly, so as not to interfere with consumer activities that can cause negative perceptions. Then consistency to always maintain the quality of content from the information presented by the detikcom site, so that consumer trust in accessing the detikcom site continues to increase. This study will help advertising managers on online media related to consumer views, to strive for marketing effectiveness through advertising displays so that they can work optimally.